Telaah Literatur Sistematis Intervensi Dalam Usaha Meminimalisir Quarter Life Crisis - Wibisono, Gunawan; Hakim, Zun Azizul (Happiness: Journal of Psychology and Islamic Science, 2022)
Early adulthood is the transition period from adolescence to adulthood. This is a complex transitional phase. There are so many stressors that lead to various difficulties, which cause individuals to feel trapped and lose their way into adulthood. This condition is known as a quarter-life crisis which is a common phenomenon that occurs between the ages of 18 to 30. The purpose of this study is to examine various alternative interventions that can be used to minimize quarter-life crises in early adulthood. The method used in this research is a systematic literature review. Researchers chose 7 out of 13 articles found on the Google Scholar search engine in the 2011-2021 timeframe. Interventions for quarter-life crises are carried out both preventively and curatively. Domination interventions that have been studied by previous researchers are mostly curative. The number of research subjects involved in the study varied from 2 respondents to 531 respondents. The research methods used also vary, both in the form of qualitative and quantitative research (experiments). This shows that research on interventions for quarter-life crises is still developing and open to new findings.